Ukraine in the creative ideas of Olexander Griboiedov (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
This article is about that the main purpose of Aleksandr Griboedov's journey to Kyiv and Crimea in summer in 1825 was related probably not to decembrist businesses, what some researchers assert about, but with a desire to collect material for new artis-tic works in basis of which there must be episods from the history of Ukraine.
Keywords: episods; plot